Syngas Production via Ethanol Dry Reforming: Effect of Promoter Type on Al2O3-supported Co Catalysts - Fayaz, Fahim; Mahadi, Bahari; Nguyen-Phu, Huy; Nguyen-Huy, Chinh; Bawadi, Abdullah; Vo, Dai-Viet N. (2017)
Lanthanide-promoted (ceria and lanthana) and unpromoted 10%Co/Al2O3 catalysts were synthesized via co-impregnation technique and evaluated for ethanol dry reforming in a quartz fixed-bed reactor at PCO2 = PC2H5OH = 20 kPa and reaction temperature of 973 K under atmospheric pressure. Both Co3O4 and CoAl2O4 phases were formed on the surface of promoted and unpromoted catalysts. The reduction of Co3O4 to CoO phase was facilitated by CeO2 or La2O3 addition. C2H5OH conversion improved significantly up to about 1.2 and 1.9 times with the addition of CeO2 and La2O3 promoters, respectively. La-promoted catalyst appeared to be the best catalyst in terms of H2 and CO yields as well as C2H5OH conversion followed by Ce-promoted and unpromoted catalysts.